2012
DOI: 10.1055/s-0032-1306300
|View full text |Cite
|
Sign up to set email alerts
|

Early Exposure to a High-Fat Diet has more Drastic Consequences on Metabolism Compared with Exposure During Adulthood in Rats

Abstract: The aim of this study was determine whether the introduction of a high-fat diet during the peripubertal phase induces significant changes in body weight control, glucose homeostasis and the parasympathetic tonus compared with the administration of this diet to adult rats. High-fat diet was offered to male Wistar rats at weaning or during adulthood. A group of rats received high-fat diet for 60 days, from weaning to 81-day-old (HF81) or from 60 to 120-day-old (HF120), whereas 2 other groups received a normal-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 15 publications
3
31
1
Order By: Relevance
“…Rodrigues et al showed that obese animals given early over-nutrition display impaired insulin signaling with low IRS-1 and PI3K levels and, consequently, a decrease in insulin sensitivity [33]; these results confirm our findings from the ivGTT and ipITT tests. We showed that HFD-SED rats were resistant to insulin when compared to Control-SED animals, as has been observed in other studies [8,13]. The development of insulin resistance was inhibited by moderate exercise in the HFD-EXE group in contrast to the respective sedentary group (HFD-SED).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Rodrigues et al showed that obese animals given early over-nutrition display impaired insulin signaling with low IRS-1 and PI3K levels and, consequently, a decrease in insulin sensitivity [33]; these results confirm our findings from the ivGTT and ipITT tests. We showed that HFD-SED rats were resistant to insulin when compared to Control-SED animals, as has been observed in other studies [8,13]. The development of insulin resistance was inhibited by moderate exercise in the HFD-EXE group in contrast to the respective sedentary group (HFD-SED).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, our group showed that HFD introduced during adolescence causes more drastic consequences in metabolism than when HFD was administered in adult rats [13]. As with gestation and/or lactation, adolescence is a very sensitive phase in brain development; and any injury during the peripubertal period might cause permanent changes in metabolism when the individual reaches adult life [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our group has shown that a highfat or low-protein diet administered during adolescence induces more drastic consequences on metabolism than when these diets are administered only during adulthood. 27,28 Reduced tumor cell growth, in vivo, by tumor cell transplantation, or in vitro, in cancer cell lines, was observed both in short or chronic treatment with metformin. Moreover, the antitumor effects were attributed to a direct effect of the drug, due to its concentration in the blood or in the cell culture solution.…”
Section: -25mentioning
confidence: 99%
“…[8][9][10] The pathologic complete response rate to neoadjuvant chemotherapy in diabetic patients with breast cancer was higher in patients taking metformin than in patients who had not been treated. 4,11,12 Various strategies have been reported to prevent cancer and metabolic syndrome, such as exercise training, functional food and metformin treatment, by modulating metabolism. 13,14 These strategies may support the hypothesis that some agents, such as metformin, could display some direct or indirect action on metabolism to resist further deleterious effects of tumor cell growth.…”
Section: Introductionmentioning
confidence: 99%